Critical Thinking in Biology Teacher Candidates: Hots and Influencing Factors - Sendy Putra Pradana; Muhammad Khoirul Antony; Ahmad Naharuddin Ramadhan; Advend Sri Rizky Sianturi (Smart Education, 2025)
This study aims to analyze the critical thinking skills of students in the Biology Education Study Program at Pattimura University in solving Higher Order Thinking Skills (HOTS) questions related to modern biotechnology. A descriptive research method was employed, utilizing a test instrument and unstructured interviews to identify factors influencing student performance. The measured critical thinking indicators include clarification, assessment, inference, and strategy. The analysis results indicate that the average student score was 72.5, categorized as